Implementation of E-Government In Citizen Services And Resident Registration In Banyuasin Province (Research on Application Population Management Information System) - Dian Novita Fajar Sari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Today's modern implementation of e-government requires prioritization of information technology so that online public services become more effective and efficient. In order to implement e-government in Banyuasin Provincial Population and Registry Office and provide services to municipalities, it is necessary to pay attention to what are the factors for implementing e-government. The purpose of this study is to determine the implementation of e-Government in the Banyuasin Province Population and Civil Registration Office. Use of descriptive research type qualitative research methods. Data collection techniques through observation, interviews and documentation. Data analysis process Includes data reduction, data presentation, and inference. The results of this study demonstrate his three factors in the implementation of e-government in population and registration services in Banyuasin province. 1). The supporting element is the support and desire of the Banyuasin Regency Population and Registry leadership in implementation. E-government and rules that support e-government implementations. 2). Capacity factors include the availability of financial resources from local revenue and expenditure budgets, the availability of infrastructure resources to support e-government implementations such as computers, WiFi, and printing, and the availability of personnel with capacity includes possibilities. E-Conduct government or community services online and the third). It is a value factor that the Banyuasin Regency Population and Civil Registry Service recognizes as providing online services to the community, and in the implementation of e-government, this is now a big plus in terms of effective and efficient service innovation. Influencing. The population has a service agency and a civil registration office in Banyuasin province, but the benefit felt by the community as recipients of the service is that they no longer need to come to the office to receive the service, especially if they are far away it is easy to get service from the office.